Preparation of Dosimetry of Boron Neutron Capture Therapy (BNCT) for In vivo Test Planning system using Monte Carlo N-Particle Extended (MCNP-X) Software - Muhammad Ilma Muslih Arrozaqi; Kusminarto Kusminarto; Yohannes Sardjono (Fakultas Sains dan Matematika Universitas Kristen Satya Wacana, 2016)
Cancer is a disease with second largest patients in the world. In Indonesia, the number of radiotherapy facility in Indonesia is less than 30 units and every patients needs more than single exposure, so that it result a long waiting list of treatment up to one year. Now, a new treatment of cancer is developed. It is Boron Neutron Capture Therapy that using capture reaction of neutron by Boron-10. Before this method is applied to patient, it requires some testing which is one of them is in vivo test. This research has been conducting to prepare the in vivo test, especially in dosimetry. Preparation of dosimetry includes collimator design and mouse phantom model. The optimum specification of the collimator is consist of Nickel collimator wall with 2 cm of thickness, Aluminum moderator with 10 cm of thickness and lead gamma shield with 3.5 of thickness. This design result in 1.18 x 108 n/cm2s of epithermal and thermal neutron flux, 2,24 x 10-11 Gy cm2/s of fast neutron component dose, 1.35 x 10-12 Gy cm2/s of gamma dose component, and 7.18 x 10-1 of neutron current and flux ratio. Mouse phantom model is built by two basic kind of geometry, they are Ellipsoid and Elliptical Tory. Both of basic geometry can be used to make all important organs of mouse phantom for dosimetry purpose.